ANALISIS PENGARUH DEBT TO ASSET RATIO DAN TOTAL ASSET TURNOVERTERHADAP RETURN ON EQUITY PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI PERIODE 2006-2010 - B11108113, U. RISTYARA (Jurnal Manajemen Update, 2013)
The research aimed to know the level of solvency (Debt to Assets Ratio) andthe level of activity (Total Asset Turnover), and as well as to determine the effect of the solvency (Debt to Assets Ratio) and the activity (Total Asset Turnover) to Return on Equity. The object of the research is sevenon the transport companies for the years 2006 until 2010. The research method is descriptive method. The method of analysis used is multiple linear regression analysis using SPSS version 16.0 to determine the effect of solvency (Debt to Asset Ratio) and the effect of activity (Total Asset Turnover) to Return on Equity. The results showed that the variables in this study have normal distribution. And at the multicollinearity test results also stated that there is no multicollinearity problem among the independent variables. The equation obtained from the calculation of linear regression isY= - 0,450+0,366 X1 +0,060 X2. Correlation between the Debt to Assets Ratio and Total Asset Turnoverwith Return on Equity is 0.104. This figure shows that the correlation between thesetwo variables have a positive relationship extremely low. Results of determination analysis shows that the percentage of influence of independent variables (DAR and TATO) to dependent variable (ROE) is approximately32,5%, while the remainder is equal to 67.5% influenced by other variables not included in this study. The results of analysis by F test hypotheses simultaneously conclude that DAR and TATOhas no significant effect to ROE. From t test as for the DAR and TATOhas no significant effect to ROE. Keywords : Debt to Asset Ratio, Total Asset Turnover, Return On Equity.